Measures of PHV and the effect on directional dynamic stability to identify risk factors for injury in elite football - Rhodes, D.; Maden-Wilkinson, J.; Jeffrey, J.; Birdsall, D.; Alexander, J. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The aim of this study is to analyze the relationship between peak height velocity (PHV) and dynamic balance (Y-Balance) versus non-peak growth to identify risk factors for non-contact lower limb injuries using a retrospective study design in elite youth footballers. METHODS: Ninety-three elite category 1 academy football players completed Y-Balance assessment during the preseason screening assessment. Data in relation to Y-Balance and Peak Height Velocity measures was than analyzed retrospectively and correlated against injury audit data to identify relationships between the variables. RESULTS: A significant correlation was identified between PHV and measures of directional dynamic stability utilizing Y-Balance assessment (P=0.001). No significant correlations were identified between PHV and injury or injury and dynamic stability scores (P>0.05). Injury occurrence for players within predicted periods of PHV was represented as 45%, within the cohort contained within the study. CONCLUSIONS: Evidently periods of growth and maturation within elite academy footballers has a detrimental effect on directional dynamic stability performance. However, caution must be taken with interpreting the significance of this relationship and the effect it has on injury occurrence. Consideration must be given to quantifying key etiological factors associated with injury during adolescence and refrain from reliance on measures of PHV.